Pediatric Dermatopathology - Phung, Thuy L.; Wright, Teresa S.; Pourciau, Crystal Y.; Smoller, Bruce R. (Springer International Publishing : Imprint: Springer, 2017)
This book provides practicing pathologists, dermatologists, cutaneous oncologists and dermatopathologists with a reference textbook that reviews the clinical and histopathologic features of skin disorders that affect children, along with a discussion of the molecular pathogenesis for each disease as it is currently known. The book includes a concise discussion of the clinical presentation, as well as the histologic and, when appropriate, immunohistochemical features of each disease. The book is divided into two main sections, non-neoplastic and neoplastic skin diseases. Each section is comprised of a series of chapters organized according to histologic findings rather than by clinical classification systems. This will enable the practicing pathologist to browse chapters based upon observation of routine histologic patterns. Each chapter addresses the differential diagnoses of skin disorders with focus on salient histologic characteristics. The text is richly illustrated with over 1000 colorful clinical and histologic photographs for each of the 400 entities discussed. Pediatric Dermatopathology provides a microscope table reference for the practicing pediatric pathologist, general pathologist and dermatopathologist. Further, it will serve as a reference volume for dermatologists, pediatricians and oncologic surgeons.
Keywords: Medicine.; Dermatology.; Pathology.; Surgical oncology.; elektronické knihy; electronic books